Human Dignity—A Theological and Confucian Discussion - Lo, Pilgrim W.K. (Dialog, 2009)
There is no doubt in the Christian tradition that humans are created in the image of God, which establishes the fundamental difference between humans and animals. However, problems concerning differences between humans have become more serious in theological discussions today with regard to human dignity. While theologians of the West argue for recognition of and respect for human dignity for every individual human being through legislation in the political system, one must not overlook the fact that in China, the emphasis of Confucian anthropology on the cultivation of moral personality is of vital importance for the practice and domination of politicians.